Chloride Activated Halophilic α-Amylase from Marinobacter sp. EMB8: Production Optimization and Nanoimmobilization for Efficient Starch Hydrolysis. (18th January 2015) - Kumar, Sumit; Khare, S. K.
Abstract : Halophiles have been perceived as potential source of novel enzymes in recent years. The interest emanates from their ability to catalyze efficiently under high salt and organic solvents. Present work encompasses production optimization and nanoimmobilization of an α -amylase from moderately halophilic Marinobacter sp. EMB8. Media ingredients and culture conditions were optimized by "one-at-a-time approach." Starch was found to be the best carbon source at 5% (w/v) concentration. Glucose acted as catabolic repressor for amylase production. Salt proved critical for amylase production and maximum production was attained at 5% (w/v) NaCl. Optimization of various culture parameters resulted in 48.0 IU/mL amylase production, a 12-fold increase over that of unoptimized condition (4.0 IU/mL). α -Amylase was immobilized on 3-aminopropyl functionalized silica nanoparticles using glutaraldehyde as cross-linking agent. Optimization of various parameters resulted in 96% immobilization efficiency. Starch hydrolyzing efficiency of immobilized enzyme was comparatively better. Immobilized α -amylase retained 75% of its activity after 5th cycle of repeated use.